The influence of volleyball classes on the physical fitness and health outcomes of college students - Lyudmila Shesterova; Daria Piatnytska; Lyudmila Gryshchenko; Krzysztof Wnorowski (Pedagogy of Health)
Background and Study Aim. The difficult situation in Ukraine related to military operations has created significant challenges for education and sports. This study aimed to examine the impact of volleyball training on the physical fitness and mental health of college students in this context. Physical activity and sports have been shown to have numerous benefits for both physical and mental health. The purpose of this study is to examine the impact of volleyball classes on the physical fitness and health outcomes of college students.